Electronic Educational Resources as a New Component of a Traditional Educational Process - Makhmudova, Dilfuza Melievna (Universitas Muhammadiyah Sidoarjo, 2018)
Modern educational politics of our country is directed to formation of a new type of intellect, new pedagogical paradigms of teaching and upbringing, and also to the investigating cognitive-creative potential of person. In this, electronic teaching resources, electronic libraries play great meaning (role). Electronic teaching resources help to conduct teaching in a new qualitative level. Electronic informational resources may be used as a component of traditional teaching process.